There are many ways of skinning a cat, my lord: humor in the Malaysian adversarial courtroom - Noraini Ibrahim,; Radha M.K Nambiar, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
This paper examines verbal humor in courtroom interaction in Malaysia. The adversarial courtroom is normally described as a site of struggle as disputes are presented and argued, while frames of reality are built and challenged. Social actors construct, deconstruct and reconstruct narratives and at the same time, through strategic linguistic devices attempt to maintain their profesional identities. Humor in the courtroom thus seems rather incongruous as the adversarial courtroom is usually characterized by multi-party discursive acts with both opposing parties having the aim of winning the case. The atmosphere is typically solemn and tense as lawyers ask and demand answers from witnesses, who are usually baffled by the rigors of the institutional talk. Despite this, laughter and humor are present at certain times and during certain occasions. The question is when is humor appropriate in a context of power asymmetry and contestations? Further, can humor in the Malaysia multi-cultural context reveal other strategies that are culturally oriented?